2015
DOI: 10.2527/jas.2015-8913
|View full text |Cite
|
Sign up to set email alerts
|

Stocking rate and monensin supplemental level effects on growth performance of beef cattle consuming warm-season grasses1

Abstract: The objective of this study was to evaluate the effects of monensin supplementation on animals receiving warm-season grass with limited supplementation. In Exp. 1, treatments were a factorial combination of 2 stocking rates (1.2 and 1.7 animal unit [AU] [500 kg BW]/ha) and supplementation with monensin (200 mg/d) or control (no monensin) distributed in a complete randomized design with 3 replicates. Thirty Angus × Brahman crossbred heifers (Bos taurus × Bos indicus) with initial BW of 343 ± 8 kg were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
5
8
0
4
Order By: Relevance
“…The average monensin dose used in the experiments was 28.1mg per kg of diet and a linear effect was observed for ADG with increasing ionophores dose. Vendramini et al (2015) evaluated the effects of monensin in crossbreed Angus x Brahman heifers kept in Paspalum notatum pasture with a concentrate supplementation restricted to 400mg/animal, day -1 and did not observe differences in ADG between animals supplemented or not with monensin (200mg/animal, day -1 ), corresponding to 58mg per 100kg BW, a dose above the one consumed by animals in the present study, but with similar results. Vendramini et al (2015) also tested 0, 14.5, 29.0 and 43.5mg of monensin per kg of DMI, using cannulated young bulls, consuming 0.2% of BW of hay and concentrate.…”
Section: Resultssupporting
confidence: 74%
“…The average monensin dose used in the experiments was 28.1mg per kg of diet and a linear effect was observed for ADG with increasing ionophores dose. Vendramini et al (2015) evaluated the effects of monensin in crossbreed Angus x Brahman heifers kept in Paspalum notatum pasture with a concentrate supplementation restricted to 400mg/animal, day -1 and did not observe differences in ADG between animals supplemented or not with monensin (200mg/animal, day -1 ), corresponding to 58mg per 100kg BW, a dose above the one consumed by animals in the present study, but with similar results. Vendramini et al (2015) also tested 0, 14.5, 29.0 and 43.5mg of monensin per kg of DMI, using cannulated young bulls, consuming 0.2% of BW of hay and concentrate.…”
Section: Resultssupporting
confidence: 74%
“…Fighting for feed is a behaviour that may cause higher feed competition. The results of this study are consistent with other studies that reported similar results in the performance of growing heifers (Vendramini et al 2015) and dairy cattle (Lobeck-Luchterhand et al 2015). Hanwoo calves are social animals and thus higher numbers of calves in one group may increase fighting behaviour in calves as we observed in this study.…”
Section: Growth Performancesupporting
confidence: 93%
“…Fereli et al (2010) também não observaram diferenças no pH ruminal de bovinos com o uso de levedura e monensina. A monensina tem sido identificada causar aumento do pH ruminal em dietas ricas em concentrado (SAFAEI et al, 2014), mas não em bovinos sob pastejo ou em dieta rica em forragem (DEMARCO et al, 2014;VENDRAMINI et al, 2015). Houve diminuição no valor médio do pH de antes da alimentação (6,62) para 4 h após (6,47).…”
Section: Resultsunclassified
“…A concentração de nitrogênio amoniacal no rúmen foi reduzida com a adição de monensina (13,77mg/dL) em relação à dieta controle (16,48mg/dL) (Tabela 4). Entretanto, pesquisadores não observaram efeitos da monensina na produção de N-amoniacal no rúmen em bovinos (FERELI et al, 2010;VENDRAMINI et al, 2015). Em dieta de baixa qualidade de forragem a adição de levedura tem sido observada causar redução na concentração de N-amoniacal no rúmen (MAO et al, 2013).…”
Section: Resultsunclassified
See 1 more Smart Citation